PENGARUH VARIABEL MONETER TERHADAP INDEKS HARGA SAHAM SEKTOR KEUANGAN DI INDONESIA: ERROR CORRECTION MODEL - Florentinus Nugro Hardianto (Universitas Islam Indonesia, 2008)
The aim of this research is to analyse the effect of monetary variables on financial sector composite index in Indonesia by using error correction model for 1997:1-2006:4 period. The result of cointegration test shows that there is a long-run or equilibrium relationship between financial sector composite index and monetary variables such as deposit interest rate, SIBOR interest rate, exchange rate, and economic growth. Both short-term and long-term, financial sector composite index are influenced by exchange rate significantly. Implication of this research is that exchange rate stabilization policy can affect Indonesian capital market growth, especially in financial sector.Keywords: financial sector composite index, monetary variable, error correction model